Vancomycin resistance is encoded on a pheromone response plasmid in Enterococcus faecium 228. - Handwerger, S (1990)
In Enterococcus faecium 228, vancomycin resistance is encoded on a 55-kilobase conjugative plasmid, pHKK100. This plasmid was transferred with high frequency into susceptible strains of Enterococcus faecalis and conferred responses to pheromones produced by E. faecalis and Streptococcus sanguis. pHKK100 is the first plasmid described that mediates both vancomycin resistance and pheromone response.